2008
DOI: 10.1038/ejhg.2008.171
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a prostate cancer susceptibility gene on chromosome 5p13q12 associated with risk of both familial and sporadic disease

Abstract: Genetic heterogeneity is a difficulty frequently encountered in the search for genes conferring susceptibility to prostate cancer. To circumvent this issue, we selected a large prostate cancer pedigree for genome-wide linkage analysis from a population that is genetically homogeneous. Selected cases and first-degree relatives were genotyped with Affymetrix 10K SNP arrays, identifying a 14 Mb haplotype on chromosome 5 (5p13-q12) inherited identical-by-descent (IBD) by multiple cases. Microsatellite genotyping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…With the completion of the human genome project, high‐throughput genomic analysis platforms now permit identification of candidate cancer risk genes in large population studies 1‐3. This technology may be particularly helpful in diseases such as prostate cancer, where no dominant singular oncogenes have emerged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the completion of the human genome project, high‐throughput genomic analysis platforms now permit identification of candidate cancer risk genes in large population studies 1‐3. This technology may be particularly helpful in diseases such as prostate cancer, where no dominant singular oncogenes have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…With the completion of the human genome project, high-throughput genomic analysis platforms now permit identification of candidate cancer risk genes in large population studies. [1][2][3] This technology may be particularly helpful in diseases such as prostate cancer, where no dominant singular oncogenes have emerged. A recent genome-wide association study identified 5 genetic variants in chromosomal regions (8q24, 3 regions; 17q12; 17q24.3) that independently or cumulatively confer susceptibility to prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, deletion of the α 2 integrin gene in cancer has not been reported. Genetic polymorphisms in the α 2 gene that potentially alter expression have been associated with prostate cancer susceptibility (46). Epigenetic modification of the α 2 gene promoter and regulation by microRNA are possibilities, since there is a progressive loss of expression in humans as tumor cells become less differentiated.…”
Section: Figurementioning
confidence: 99%
“…FitzGerald et al. [119] have selected a large prostate cancer pedigree for a genome‐wide linkage analysis from a population that is genetically homogeneous. They found a 14Mb haplotype at chromosome 5p13–q12.…”
Section: Chromosomal Locimentioning
confidence: 99%